PERILAKU KONSUMTIF MAHASISWA: PERAN LITERASI KEUANGAN DAN ELECTRONIC WALLET - Siti Maryam; Esti Dwi Rahmawati; Taufiq NM (Kampus Akademik Publiser, 2024)
This research aims to strengthen and prove whether financial literacy can influence students' consumptive behavior. The use of e-wallet technology will also be examined to see how much influence it has on student consumption behavior with lifestyle as a moderating variable. The respondents for this research were 91 students. Data was collected using a questionnaire and analyzed using the SmartPLS 4.0 program with an outer model to assess validity and reliability, and an inner model to see the predictive power of the structural model. The results of research based on calculations using SEM-PLS show that financial literacy has a positive and not significant influence on consumer behavior, electronic wallet has a positive and significant influence on consumer behavior, financial literacy has a positive and not significant influence on consumer behavior with lifestyle as a moderator, electronic wallet has an influence Positive and Significant on Consumptive Behavior with Lifestyle as a Moderation. The implication of this research is that the application of low financial literacy and high use of electronic wallets causes high consumer behavior of students with their consumptive lifestyle. Students should apply financial literacy knowledge and be wiser in using electronic wallets in order to reduce consumer behavior and consumptive lifestyles.